2006
DOI: 10.1007/s11270-005-9040-7
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-Resistant Bacteria Associated With Macrophytes from A Polluted Lake

Abstract: Although Onondaga Lake in the Syracuse NY area is contaminated with high levels of mercury from past manufacturing operations, macrophytes in the lake have been able to survive, apparently withstanding mercury toxicity. Homogenates of three macrophyte species, Myriophyllum spicatum L., Potamogeton crispus L., and Stuckenia pectinata (L.) Borner, were phenotypically positive for the presence of mercury resistant bacteria. As determined by PCR analysis, the mercury resistant bacteria associated with M. spicatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In our study, this methodology allowed the detection of variability in the 285 bp merA fragment among 14 E. coli strains (Figure 3). These results are in agreement with previous findings regarding the widespread occurrence and diversity of mercury resistance markers among distinct microbial populations from several environments, including soils and sediments, aquatic systems, animals, and clinical isolates [13,14,27,28,31,32]. The high plasticity found in the bacterial genome contributes to the diversity and dissemination of genetic markers favoring its circulation in geographically dispersed environments, even between distinct evolutionary lineages.…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)supporting
confidence: 92%
See 1 more Smart Citation
“…In our study, this methodology allowed the detection of variability in the 285 bp merA fragment among 14 E. coli strains (Figure 3). These results are in agreement with previous findings regarding the widespread occurrence and diversity of mercury resistance markers among distinct microbial populations from several environments, including soils and sediments, aquatic systems, animals, and clinical isolates [13,14,27,28,31,32]. The high plasticity found in the bacterial genome contributes to the diversity and dissemination of genetic markers favoring its circulation in geographically dispersed environments, even between distinct evolutionary lineages.…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)supporting
confidence: 92%
“…Considering the genetic of MerA expression, the Hg resistance (mer) operon presents a fundamental role in regulation, Hg binding, and organomercury degradation. It consists of essential genes as merR (responsible for the regulation of the operon), merT/merP (transport of mercury into the bacterial cell), merA (reduction of ionic mercury), and accessory genes such as merB, merC, merD, merE, merF, and merG, that encode proteins that add other skills to microorganisms [13,14]. MerR protein can act both as a repressor and activator of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these inoculations were carried out in soil plants rhizosphere to recover metal contaminated soils and studies with wetlands plants are to our knowledge almost inexistent. In fact, only two studies have shown rhizobacteria could be important in the accumulation and attenuation of toxicity of Hg to salt marsh plants ( de Souza et al, 1999;Caslake et al, 2006). But very recently a study by the authors showed autochthonous bioaugmentation with Cd resistant microorganisms could be useful for enhancement of P. australis phytoremediation potential for Cd contaminated estuarine sediments (Nunes da Silva et al, 2014).…”
Section: Metal Speciationmentioning
confidence: 99%
“…Although the importance of the rhizosphere community for plant development in contaminated soils has been recognized, nothing is known about this aspect in S. maritima. Actually, the information is scarce in wetland plants in general [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%